2019
DOI: 10.1016/j.ygeno.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional profile through cell cycle progression in Arabidopsis cultures under simulated microgravity

Abstract: Plant cell proliferation is affected by microgravity during spaceflight, but involved molecular mechanisms, key for space agronomy goals, remain unclear. To investigate transcriptomic changes in cell cycle phases caused by simulated microgravity, an Arabidopsis immobilized synchronous suspension culture was incubated in a Random Positioning Machine. After simulation, a transcriptomic analysis was performed with two subpopulations of cells (G2/M and G1 phases enriched) and an asynchronous culture sample. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The cell cycle is an essentially biological process ( 18 , 19 ). Under normal conditions, cells proliferate only in response to mitotic signals, which are more significant for normal organisms, while the proliferation of cancer cells is out of control ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle is an essentially biological process ( 18 , 19 ). Under normal conditions, cells proliferate only in response to mitotic signals, which are more significant for normal organisms, while the proliferation of cancer cells is out of control ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…To complement the experiments on plant seedlings, further research has taken advantage of cell culture in ground-based space simulation conditions to address fundamental mechanistic and functional questions. Several transcriptomic publications from a research group in Madrid ( Herranz et al., 2013a ; Kamal et al., 2019a , 2019b ; Manzano et al., 2012 ) have shown that basic parameters of cell proliferation and cell division control are dysregulated under altered gravity conditions. Fundamental mechanisms, such as chromatin remodeling, are affected under these conditions, and should be tested in spaceflight experiments (i.e., true microgravity).…”
Section: Esa-(co)funded Omics Workmentioning
confidence: 99%
“…Physiological and cellular alterations are related to changes in gene expression, which have been identified by transcriptomic studies from space and ground experiments (Paul et al, 2012;Kwon et al, 2015;Johnson et al, 2017;Paul et al, 2017;Choi et al, 2019;Herranz et al, 2019;Kamal et al, 2019;Vandenbrink et al, 2019;Kruse et al, 2020;Villacampa et al, 2021a). In some cases, complementary proteomic studies were also performed (Kruse et al, 2020).…”
Section: Plants and Gravity Plant Response And Acclimation To Microgravitymentioning
confidence: 99%